Development and evaluation of an evidence-based, theory-grounded online Clinical Frailty Scale tutorial. (7th February 2022) - Haddad, Taleen; Mulpuru, Sunita; Salter, Ivy; Hladkowicz, Emily; Des Autels, Kathryne; Gagne, Sylvain; Bryson, Gregory L; McCartney, Colin J L; Huang, Allen; Huang, Shirley; Forster, Alan; van Walraven, Carl; et al.
Abstract: Introduction: Frailty is a robust predictor of adverse outcomes in older people. Practice guidelines recommend routine screening for frailty; however, this does not occur regularly. The Clinical Frailty Scale (CFS) is a validated, feasible instrument that can be used in a variety of clinical settings and is associated with many adverse outcomes. Our objective was to develop and evaluate an online training module to guide frailty assessment using the CFS. Methods: A multidisciplinary team of clinical experts developed an evidence-based, theory-grounded online training module for users who wished to perform frailty assessment using the CFS. The module was prospectively evaluated for user satisfaction, effectiveness and feasibility using a standardised questionnaire. Qualitative feedback was analysed with thematic analysis. Results: Version 1 of the CFS module was used 627 times from 21 October 2019 to 24 March 2020. Satisfaction, effectiveness and feasibility of the module were positively rated (≥4/5 on a 5-point Likert scale n  = 582 [93%], n  = 507, [81%], n  = 575, [91%], respectively). Qualitative feedback highlighted ease of use, likelihood of users to share the module with others and opportunities to increase multimedia content. Conclusion: An online tutorial, designed using evidence and theory to guide frailty assessment using the CFS, was positively rated by users. The module's content and structure was rated effective and feasible, and users were satisfied with, and likely to share, the module. Research evaluating the module's impact on the accuracy of frailty assessment is required.